Bonobo anatomy reveals stasis and mosaicism in chimpanzee evolution, and supports bonobos as the most appropriate extant mode﻿l for the common ancestor of chimpanzees and humans - Rui Diogo; Julia L. Molnar; Bernard Wood (Scientific Reports, 2017)
Abstract Common chimps and bonobos are our closest living relatives but almost nothing is known about bonobo internal anatomy. We present the first phylogenetic analysis to include musculoskeletal data obtained from a recent ﻿dissection of bonobos. Notably, chimpanzees, and in particular bonobos, provide a remarkable case of evolutionary stasis for since the chimpanzee-human split c.8 Ma among >120 head-neck (HN) and forelimb (FL) muscles there were only four minor changes in﻿ the chimpanzee clade, and all were reversions to the ancestral condition. Moreover, since the common chimpanzee-bonobo split c.2 Ma there have been no changes in bonobos, so with respect to HN-FL musculature bonobos are the better model for the last common ancestor (LCA) of chimpanzees/bonobos and humans. Moreover, in the hindlimb there are only two muscle absence/presence differences between common chimpanzees and bonobos. Puzzlingly, there is an evolutionary mosaicism between each of these species and humans. We discuss these data in the context of available genomic information and debates on whether the common chimpanzee-bonobo divergence is linked to heterochrony.